1978
DOI: 10.1093/bja/50.6.575
|View full text |Cite
|
Sign up to set email alerts
|

Combined I.V. Bolus and Infusion of Pancuronium Bromide

Abstract: SUMMARYAn i.v. bolus and concomitant infusion of pancuronium is proposed for use in prolonged anaesthesia. Plasma concentrations of pancuronium were measured in 16 patients receiving this regime. The desired steady-state concentration of 0.2 fig ml" 1 was achieved in most instances at approximately 45 min. Following the bolus, the neuromuscular twitch response decreased to low values or was abolished completely. Thereafter the response remained relatively constant or increased in intensity consistent with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The relative potency of pancuronium, alcuronium and tubocurarine found in this study is in accord with previous animal studies (Cass et al, 1976;Booij et al, 1980) and human studies (Lund and Stovner, 1970;Donlon, Ali and Savarese, 1974) and with clinical experience (Baird and Reid, 1967;Baird, 1968;Crul, 1970;Levin and Dillon, 1971). Somogyi, Shanks and Triggs (1978) calculated the amount of a bolus injection of pancuronium producing an almost complete block to be 62.5 ng kg" 1 body weight. This is almost identical with our finding (62.2 ±4.9 (xg kg-1 )-The relative potency of Org NC 45 to pancuronium (1.7) in this study differs from that reported by Agoston and others (1980), who found the drugs to be equipotent.…”
Section: Discussionmentioning
confidence: 99%
“…The relative potency of pancuronium, alcuronium and tubocurarine found in this study is in accord with previous animal studies (Cass et al, 1976;Booij et al, 1980) and human studies (Lund and Stovner, 1970;Donlon, Ali and Savarese, 1974) and with clinical experience (Baird and Reid, 1967;Baird, 1968;Crul, 1970;Levin and Dillon, 1971). Somogyi, Shanks and Triggs (1978) calculated the amount of a bolus injection of pancuronium producing an almost complete block to be 62.5 ng kg" 1 body weight. This is almost identical with our finding (62.2 ±4.9 (xg kg-1 )-The relative potency of Org NC 45 to pancuronium (1.7) in this study differs from that reported by Agoston and others (1980), who found the drugs to be equipotent.…”
Section: Discussionmentioning
confidence: 99%
“…The relative potency of pancuronium, alcuronium and tubocurarine found in this study is in accord with previous animal studies (Cass et al, 1976;Booij et al, 1980) and human studies (Lund and Stovner, 1970;Donlon, Ali and Savarese, 1974) and with clinical experience (Baird and Reid, 1967;Baird, 1968;Crul, 1970;Levin and Dillon, 1971). Somogyi, Shanks and Triggs (1978) calculated the amount of a bolus injection of pancuronium producing an almost complete block to be 62.5 ng kg" 1 body weight. This is almost identical with our finding (62.2 ±4.9 (xg kg-1 )-The relative potency of Org NC 45 to pancuronium (1.7) in this study differs from that reported by Agoston and others (1980), who found the drugs to be equipotent.…”
Section: Discussionmentioning
confidence: 99%